2020
DOI: 10.1039/d0qi00792g
|View full text |Cite
|
Sign up to set email alerts
|

Constructing [CoII6] hexagon-centered heterometallic {Ln6Co6} (Ln = Y, Eu and Dy) clusters with a calix[8]arene ligand

Abstract: Three isostructural 3d-4f polynuclear clusters {(LnIII6CoII6)(C8A)3} (Ln= Y(CIAC-248), Eu(CIAC-249), Dy(CIAC-250); C8A = p-tert-butylcalix[8]arene) were synthesized under solvothermal conditions. These three compounds are featured with some tripod-like entities in which threeLn2-C8A...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…24,25 Several conformations of TBC [8] have been observed in the transition metal (TM) or lanthanide metal complexes based on TBC [8], including pleated-loop, double-cone, and inverted double-cone. 20,21,[26][27][28] In particular, TBC [8] that adopts the double-cone conformation can form the Ln 2 -TBC [8] subunit upon reaction with Ln 3+ ions. 29 However, we do not know the conformation in which TBC [8] combines with Zr 4+ (Hf 4+ ) to form the hierarchical structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Several conformations of TBC [8] have been observed in the transition metal (TM) or lanthanide metal complexes based on TBC [8], including pleated-loop, double-cone, and inverted double-cone. 20,21,[26][27][28] In particular, TBC [8] that adopts the double-cone conformation can form the Ln 2 -TBC [8] subunit upon reaction with Ln 3+ ions. 29 However, we do not know the conformation in which TBC [8] combines with Zr 4+ (Hf 4+ ) to form the hierarchical structure.…”
Section: Introductionmentioning
confidence: 99%
“…17 Based on the multiple hydroxyl groups of TBC [8], Dalgarno, Liao and other groups have reported a series of MOCs, including Gd 8 , Pr 10 , Ln 6 Cr, Ln 6 Co 6 and Pb 12 . [18][19][20][21][22] In addition, bulky calixarenes provide a rigid shell to protect the metal core, and the continuous carbon backbone structure can increase the stability of the clusters. 17,23 However, calixarene-protected ZrOCs (HfOCs) are rare, and the crystal structure of calix [8]arene-based ZrOCs (HfOCs) has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, molecule-based magnetic materials have attracted extensive attention due to their important properties and potential application prospects. Among them, the 3d–4f heterometallic complexes exhibit various structures and excellent magnetic properties which are significant in both crystal engineering and magnetism investigations. Many 3d–4f complexes with finite nuclear clusters and infinite structure chains, layers, and networks have been synthesized with different strategies. ,, In the high-nuclear clusters or coordination polymers, it is found that some 3d–4f clusters have small nuclearity as building blocks, which are connected to each other through the 4f ions. , However, the connections that are not conducive to transfer magnetic interactions for 4f electrons are inner shell electrons and are not coupled effectively with other spin carriers . To avoid the above problems, small 3d–4f clusters should be connected by a “magnetic bridge” through the 3d ions.…”
Section: Introductionmentioning
confidence: 99%
“…Relative to the extensive research on the synthesis and properties of Ni-Ln, other high-nuclearity 3d-Ln clusters are less studied, owing to the di culty of synthesis [38][39] . Co ions with the high spin ground state and excellent catalysis have been widely studied [40][41][42][43][44] It is worth noting that a large series of CO 3 2− anions as important templates and linkers among metal ions, deriving from the decomposition of organic ligands, exhibit a rich variety of coordination modes (Fig. S3), re ecting the complexity of the nanocluster structure, and the adaptability of the anion templates.…”
Section: Introductionmentioning
confidence: 99%